Changes in the gene expression and gut microbiome to the infection of decapod iridescent virus 1 in Cherax quadricarinatus. Issue 132 (January 2023) - Zheng, Jianbo; Jia, Yongyi; Li, Fei; Chi, Meili; Cheng, Shun; Liu, Shili; Jiang, Wenping; Liu, Yinuo
Abstract: As a new emerging viral pathogen, Decapod iridescent virus 1 (DIV1) seriously threatens crustacean farming in recent years. However, limited research progresses have been made on the immune mechanism between host and viral factors in response to DIV1 infection. In the current study, a natural occurrence of DIV1 infection with obvious clinical signs was found in farmed redclaw crayfish Cherax quadricarinatus, and confirmed by nested PCR detection and histopathological examination. Besides, gene expression profiles were analyzed after being challenged with DIV1, and results showed that 27 immune related genes were upregulated compared with the control group. Moreover, the gut microbiota from healthy and DIV1-infected crayfish were investigated by 16S rDNA high-throughput sequencing. Results showed that significant differences in the microbial composition and function were observed after DIV1 challenge. Furthermore, we discovered that changes in gene expression profiles were correlated with microbiota alterations under DIV1 challenge. Taken together, our findings will provide new insights into the immune response mechanism of DIV1 infection in crustaceans. Highlights: DIV1 infection was found in farmed redclaw crayfish by nested PCR detection and histopathological examination . Significant difference was observed within the composition and function of gut microbiota after being challenged with DIV1 . A high correlation between bacterial genera and immune genes was observed between healthy and DIV1-infected crayfish.